2016
DOI: 10.1007/s12041-016-0645-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetic analysis of four species of Dendropsophus (Hylinae) from the Brazilian Atlantic forest

Abstract: We conducted a cytogenetic study of four hyline frog species (Dendropsophus elegans, D. microps, D. minutus and D. werneri) from southern Brazil. All species had 2n = 30 chromosomes, with interspecific and intraspecific variation in the numbers of metacentric, submetacentric, subtelocentric and telocentric chromosomes. C-banding and fluorochrome staining revealed conservative GC-rich heterochromatin localized in the pericentromeric regions of all species. The location of the nucleolus organizer regions, as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In addition to the diploid number, the NORs and 18S sequences have conserved characteristics and are found at the same loci in species within these genera or within species groups (see references in online suppl. material) [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the diploid number, the NORs and 18S sequences have conserved characteristics and are found at the same loci in species within these genera or within species groups (see references in online suppl. material) [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although all of the Dendropsophus species karyotyped to date show 2n = 30 (see review in Catroli and Kasahara 2009, Medeiros et al 2013, Suárez et al 2013, Oliveira et al 2016), a noticeable variation in the number of biarmed/telocentric chromosomes is observed among them, suggesting that several chromosomal rearrangements took place after the evolutionary origin of the hypothetical ancestral 30-chromosome karyotype. Karyotypes with only biarmed chromosomes [as in Dendropsophus minutus (Peters, 1872) (Gruber et al 2005) and Dendropsophus leali (Bokermann, 1964) (Bogart 1973)] and karyotypes with up to five pairs of telocentric/subtelocentric chromosomes [as in Dendropsophus labialis (Peters, 1863) (Bogart 1973), Dendropsophus sanborni (Schmidt, 1944) and Dendropsophus jimi (Napoli & Caramaschi, 1999) (Medeiros et al 2013)] may be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine species groups recognized in Dendropsophus (for a review of the Dendropsophus groups, see Faivovich et al 2005), the Dendropsophus microcephalus (Cope, 1886) group is the most species-rich (currently with 40 species—Frost 2016) and the most studied cytogenetically (17 species karyotyped—review by Catroli and Kasahara 2009, Medeiros et al 2013, Oliveira et al 2016). It is noteworthy that karyotypes without any telocentric chromosome (in Dendropsophus leali —Bogart 1973) and with one [as in Dendropsophus bipunctatus (Spix, 1824)—Bogart 1973], two [as in Dendropsophus phlebodes (Steineger, 1906)—Kaiser et al 1996], three [as in Dendropsophus cruzi (Pombal & Bastos, 1998)—Gruber et al 2005], four [as in Dendropsophus nanus (Boulenger, 1889)—Medeiros et al 2003] or five (as in Dendropsophus jimiMedeiros et al 2013) telocentric chromosome pairs are observed in this group.…”
Section: Introductionmentioning
confidence: 99%
“…Although all of the Dendropsophus species karyotyped to date show 2n = 30 (see review in Catroli and Kasahara 2009, Medeiros et al 2013, Suárez et al 2013, Oliveira et al 2016), a noticeable variation in the number of biarmed/telocentric chromosomes is observed among them, suggesting that several chromosomal rearrangements took place after the evolutionary origin of the hypothetical ancestral 30-chromosome karyotype. Karyotypes with only biarmed chromosomes [as in D. minutus (Peters, 1872) (Gruber et al 2005) and D. leali (Bokermann, 1964) (Bogart 1973)] and karyotypes with up to five pairs of telocentric/subtelocentric chromosomes [as in D. labialis (Peters, 1863) (Bogart 1973), D. sanborni (Schmidt, 1944) and D. jimi (Napoli & Caramaschi, 1999) (Medeiros et al 2013)] may be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine species groups recognized in Dendropsophus (for a review of the Dendropsophus groups, see Faivovich et al 2005), the D. microcephalus (Cope, 1886) group is the most species-rich (currently with 40 species-Frost 2016) and the most studied cytogenetically (17 species karyotyped-review by Catroli and Kasahara 2009, Medeiros et al 2013, Oliveira et al 2016. It is noteworthy that karyotypes without any telocentric chromosome (in D. leali-Bogart 1973) (Bogart 1973, Kaiser et al 1996, Gruber et al 2005, which currently has 11 species (see Frost 2016) and is the second most cytogenetically studied species group of Dendropsophus (four of the named species are karyotyped).…”
Section: Introductionmentioning
confidence: 99%